The effect of a genre-based pedagogical approach on Orang Asli students’ EFL writing performance - Ganapathy, Malini; Kaur, Manjet; Jamal, Marlina; Phan, Jonathan (Universiti Utara Malaysia Press, 2022)
Purpose – In the 21st century, the importance of having good English proficiency in Malaysia and globally has impacted educators, especially in terms of their pedagogical practices. Although students are exposed to 11 years of English language instruction in Malaysia, Orang Asli students still possess low English proficiency and poor writing skills. This study aims to determine the extent to which the genre-based pedagogical approach is able to improve Orang Asli students’ English as a foreign language (EFL) writing performance and analyse their responses in using the genre-based pedagogical approach as a framework to improve their EFL writing performance.